EFEKTIVITAS PROGRAM AKU WARAS SEBAGAI SISTEM PELAYANAN ADMINISTRASI KEPENDUDUKAN ONLINE DI DISDUKCAPIL KOTA DENPASAR - Sarifah, Melati Putri; Supriliyani, Ni Wayan; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2023)
The Population and Civil Registration Service of Denpasar City began to implement online services in the form of the AKU WARAS program, with the aim of providing ease of population administration management regulated in Permendagri No.7 of 2019 concerning Online Population Administration Services. This research uses a qualitative type of research with a descriptive approach. The data sources used are primary and secondary data. Informant Determination Technique using purposive sampling. The results showed that the effectiveness of the AKU WARAS program at the Denpasar City Population and Civil Registration Service was categorized as having been carried out properly, but not yet fully effective. Because, the socialization about the AKU WARAS program is not optimal, there are still many people who do not know about the existence of the AKU WARAS program. The main objective of the program to provide effective and efficient services is still not well implemented. Keywords: Program Effectiveness, Population Administration Services, AKU WARAS Program